(untitled) (Fiep Bulletin - online, 2014)
The Extension Project "Physical Activities and Inclusive Sport" has the objective to develop activities for People with Special Necessities through the adaptation of the most varied practices for reality and the necessities of the involved groups. Among the developed activities, we report here the initial experience of the group of inclusion to the aquatic environment directed the people with visual deficiency, in the sense to understand the perceptions of the coordinators, professors and participants of the project.This study intends to explicit, even in succinct away, a description on suitable physical activity, as well as approaching aspects of the visual deficiency in the context of the aquatic activity. Analyzing the data of the participants, manifestations of satisfaction, joy had been observed and accomplishment to be exercising some movements in the water, at last, to be able to find a space to do physical activity, contributing to the motor, affective and social development.Regarding the professors it was contextualized that the proposed activities contribute to an effective process of improvement of the quality of life, leisure and integration of the participants. Due to the given information we can underline that, to look at the people who present different and peculiar conditions for the practice of physical activities, to understand its limitations and to respect the individuality, is the essential when it is about the diversity, either in the professional, educational and sportive sector.